Study of the effect of balloon sinuplasty in patients with rhinosinusitis - Singh, Tanya; Singh, Arjun; Singh, Sarbjeet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: A new technique which has revolutionized sinus surgery recently is balloon sinuplasty. The vast majority of patients with chronic rhinosinusitis improve with medical management, including antibiotics, saline irrigation, nasal steroids, antihistamines, allergy therapy, and asthma control. This study was conducted to study the effect of balloon sinuplasty in patients affected with rhinosinusitis. Methods: This prospective study was conducted in all the patients visiting our hospital. Medical treatment included oral and sometimes intravenous antibiotics, nasal steroids, decongestants, systemic steroids, and allergy management. Those who had a positive biopsy were excluded from this study. The selected cohort of 20 patients, were prepared for balloon sinuplasty surgery in the same way as for conventional functional endoscopic sinus surgery (FESS) and were operated by our surgical team. Results: 20 patients were included in the study, 70% men and aged 30±12 years. Sinuplasty was performed in 32 sinuses of 20 patients (22 maxillary, 4 sphenoid and 8 frontal sinuses). Conclusions: Sinuplasty with balloon catheterization is effective in reducing symptoms and improving quality of life in selected patients with chronic rhinosinusitis. The results are beyond reported symptoms and confirm the benefit of balloon sinuplasty.